Improving student assessment feedback in an introductory accounting course through two-stage collaborative assessment - Kruger, S.J. (South African Journal of Higher Education, 2020)
Student feedback is an important part of the formative assessment process. Previous research shows that there is room for improvement in student feedback on accounting education. Various benefits, especially those associated with the development of certain pervasive skills through cooperative learning, have been established through research. The two-stage group examination offers students the opportunity to become active participants in the feedback process, while harvesting the benefits of teamwork. This study involving 24 students enrolled for an introductory accounting course evaluated the efficacy of the two-stage examination as an intervention to improve feedback. Students perceived that examination retakes in a team environment were helpful to establish where they made mistakes and showed them how they could improve their future performance. They could further establish how they performed compared to their peers. The examination retakes also helped to improve their understanding of the work and how they could improve their learning. The intervention was well received by students despite reports of free riding. This study adds to the limited body of research on two-stage exams in accounting education.